Inhibition of Histone Deacetylases Prevents Cardiac Remodeling After Myocardial Infarction by Restoring Autophagosome Processing in Cardiac Fibroblasts - Yaping Wang; Panpan Chen; Lihan Wang; Jing Zhao; Zhiwei Zhong; Yingchao Wang; Jifeng Xu (Cellular Physiology and Biochemistry, 2018)
Background/Aims: Histone deacetylases (HDACs) play a critical role in the regulation of gene transcription, cardiac development, and diseases. The aim of this study was to investigate whether the inhibition of HDACs improves cardiac remodeling and its underlying mechanisms in a mouse myocardial infarction (MI) model. Methods: The HDAC inhibitor trichostatin A (TSA, 0.1 mg/kg/day) was administered via daily intraperitoneal injections for 8 consecutive weeks after MI in C57/BL mice. Echocardiography and tissue histopathology were used to assess cardiac function. Cultured neonatal rat cardiac fibroblasts (NRCFs) were subjected to simulated hypoxia in vitro. Autophagic flux was measured using the tandem fluorescent mCherry-GFP-LC3 assay. Western blot was used to detect autophagic biomarkers. Results: After 8 weeks, the inhibition of HDACs in vivo resulted in improved cardiac remodeling and hence better ventricular function. MI was associated with increased LC3-II expression and the accumulation of autophagy adaptor protein p62, indicating impaired autophagic flux, which was reversed by TSA treatment. Cultured NRCFs exhibited increased cell death after simulated hypoxia in vitro. Increased cell death was associated with markedly increased numbers of autophagosomes but not autolysosomes, as assessed by punctate dual fluorescent mCherry-green fluorescent protein tandem-tagged light chain-3 expression, indicating that hypoxia resulted in impaired autophagic flux. Importantly, TSA treatment reversed hypoxia-induced impaired autophagic flux and led to a 40% decrease in cell death. This was accompanied by improved mitochondrial membrane potential. The beneficial effects of TSA therapy were abolished by RNAi intervention targeting LAMP2; likewise, in vivo delivery of chloroquine abolished the TSA-mediated cardioprotective effects. Conclusion: Our results provide evidence that the HDAC inhibitor TSA prevents cardiac remodeling after MI and is dependent on restoring autophagosome processing of cardiac fibroblasts.